When living laws collide: FASB/IASB conceptual framework development as a contested discursive space - Orthaus-Wahl, Selina; Pelger, Christoph; Erb, Carsten (Accounting, Organizations and Society, 2025)
As part of their professionalisation project, independent private standard setters have developed conceptual frameworks to guide their standard setting. Adopting the perspective of legal pluralism, we regard these soft law documents as creating a new living law for the community of standard setters. In this paper, we study how the FASB and the IASB have created this new living law through the discourse on the (re)development of conceptual frameworks. More specifically, we analyse the discourse on the objective of financial reporting from the 1970s to the 2010s. Our material stems from the Boards' due process and includes their proposals, along with about 1300 comment letters submitted by constituents. We find that the FASB and the IASB have used conceptual frameworks to establish their identity as independent experts, distinguishing themselves from the accounting profession with its traditional living law of stewardship, and instead introducing the new living law of decision usefulness. This step met resistance as constituents did not readily accept the standard setters' independence and sought to constrain their future activities. We also find that constituents’ views were influenced by the anticipated role of the conceptual frameworks for standard setters and preparers. Overall, our study shows how standard setters strategically align conceptual frameworks with the due process, while constituents simultaneously use the due process and conceptual frameworks as tools to discipline the standard setters. Our findings extend our understanding of private standard setters, conceptual frameworks, and different legal forms.